Antifungal potential of six herbal plants against selected plant fungal pathogens - Wong, Mui Yun; Hamid, Sathyapriya; Iskandar Shah, Nor Afifah; Rahim, Nur Maliya; Zainal Kasim, Zainina; Ab Razak, Nurul Husna (Universiti Putra Malaysia Press, 2020)
An investigation was conducted to determine the antifungal potential of Andrographis paniculate, Backhousia citriodora, Clinacanthus nutans, Ficus deltoidei, Phaleria macrocarpa, and Piper betle against selected plant fungal pathogens. Dilutions of crude leaf extracts (5, 10, 15, and 20%) of these plants were screened in vitro against Ganoderma boninense, Fusarium oxysporum f. sp. cubense R4 (FocR4), and Rhizoctonia solani. The percentage inhibition of diameter growth (PIDG) of test pathogens was measured using poisoned agar method. Aqueous extract of A. paniculate was ineffective in inhibiting the mycelial growth of test pathogens at all test concentrations while that of B. citriodora markedly inhibited FocR4 growth at 15% (PIDG 70%) and 20% (PIDG 72.9%) concentrations. Methanol extract of C. nutans at 20% concentration significantly inhibited R. solani growth (PIDG 64.4%) meanwhile that of P. betle at 20% considerably inhibited the growth of FocR4 (PIDG 94%), G. boninense (PIDG 89.4%), and R. solani (PIDG 82.8%). Complete inhibition (PIDG 100%) of G. boninense and R. solani was obtained at 10% concentration of F. deltoidei and P. macrocarpa methanol extracts. Leaf extracts of five herbal plants have the potential to be used as bio-fungicides as a safe alternative to synthetic fungicides.